(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Infection related complications represent an important cause of morbidity and mortality in pediatric cancer patients, especially in those receiving chemotherapy. Although antibiotic prophylaxis is used in adult leukemic patients, but it is less practiced in pediatric cancer patients. The aim of this study was to evaluate the efficacy and safety of Levofloxacin prophylaxis to reduce infection which occur during induction phase of chemotherapy among pediatric Acute Lymphoblastic Leukemia (ALL) patients. Materials and methods: This single centered, pilot study in RCT design was conducted in Pediatric HematoOncology Department of Chittagong Medical College Hospital (CMCH). Sixty newly diagnosed ALL patients admitted for chemotherapy were randomly allocated to two groups 30 in each: one group received Levofloxacin prophylaxis (Intervention group) and other group did not receive prophylaxis (Control group). During the whole period of induction, clinical and laboratory features of infection, fever and neutropenia were observed and adverse effects were noted in both groups. Results: In induction phase of chemotherapy of ALL, significantly lower proportion of patients developed fever in the intervention group than in the control group [(18/30, 60.00%) versus (26/30, 86.67%)]. Incidence of infection was significantly less in intervention group compared to control group (60% versus 86.7%, p=0.039). Also, incidence of febrile neutropenia was significantly less in intervention group compared to control group (p=0.039). No major adverse effects were observed in any of the levofloxacin prophylaxis group except only two patients reported mild lower limb pain. Conclusion: It may be concluded from this pilot study that, Levofloxacin prophylaxis in children with ALL during the induction phase of chemotherapy is effective in reducing infection, febrile episodes and febrile neutropenia. JCMCTA 2022 ; 33 (1) : 34-39